Fear of reinjury after acute Achilles tendon rupture is related to poorer recovery and lower physical activity postinjury - Elin Larsson; Agnes LeGreves; Annelie Brorsson; Pernilla Eliasson; Christer Johansson; Michael R. Carmont; Katarina Nilsson Helander (Journal of Experimental Orthopaedics)
Abstract Purpose The aim of this study was to investigate how fear of reinjury to the Achilles tendon affects return to previous levels of physical activity and self‐reported Achilles tendon Total Rupture Score (ATRS) outcomes. Methods Data were collected from a large cohort of patients treated for an acute Achilles tendon rupture at Sahlgrenska University Hospital Mölndal between 2015 and 2020. The ATRS and additional questions concerning fear of reinjury, treatment modality, satisfaction of treatment and recovery were analyzed 1–6 years postinjury. Analysis was performed to determine the impact of fear of reinjury on patient‐reported recovery and physical activity. Results Of a total of 856 eligible patients, 550 (64%) answered the self‐reported questionnaire and participated in the follow‐up. Of the participants, 425 (77%) were men and 125 (23%) were women. ATRS, recovery in percentage, satisfaction of treatment, recovery on a 5‐point scale and physical activity level post‐ versus preinjury were significantly related to fear of reinjury (p < 0.001). Of the nonsurgically treated patients, 59% reported fear of reinjury compared to 48% of the surgically treated patients (p = 0.024) Patients that reported fear of reinjury had a 15‐point lower median ATRS score than those who did not (p < 0.001). Conclusion More than half of patients who have suffered an Achilles tendon rupture are afraid of reinjuring their tendon. Patients who reported fear of reinjury exhibited a significantly lower ATRS score. This indicates the importance of addressing psychological aspects in the treatment after this injury. Level of Evidence Level II.